Glioblastoma: State of the Art and Future Perspectives (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Glioblastoma is an aggressive incurable primary tumor of the central nervous system. Median overall survival is in the range of 1.5 years even in selected clinical trials populations. Many features contribute to this therapeutic challenge including high intratumoral and intertumoral heterogeneity, resistance to therapy, migration and invasion, immunosuppression. With the access of novel highthroughput technologies, significant progress has been made to understand molecular and immunological signatures underlying the pathology of glioblastoma. Clinical trial designs have shifted from investigating broad “one-for-all” treatment approaches to precision oncology designs. The collection of contributions in this book aim at providing researchers and clinicians an update on different aspects of glioblastoma, i.e. progress in basic, preclinical and clinical research.